A Bibliometric Analysis of Remdesivir: A COVID-19 Vaccine: Bibliometric Analysis of Remdesivir - Hassan, Waseem; Ara, Amina (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
In October 2020, the U.S. Food and Drug Administration (FDA) approved remdesivir (RDV) for the treatment of COVID-19. This motivated us (a) to perform its bibliometric analysis and (b) to acknowledge the significant contribution of all researchers throughout the world. On 7th May 2021, we extracted the data from the Scopus database. Total documents were 3277, but we only analyzed 1496 articles and 1066 reviews. In all publications (n=2562), 13215 authors, 9854 departments, and 127 countries have significantly contributed. Based on Vosviewer analysis we presented the co-authorship network. Total citations for 2562 documents were 55366. The citation breakup for all documents is provided. The number of publications sources or journals was 1156. We also performed a bibliometric analysis of the top one hundred (n=100) most cited documents. Based on bibliometrix (biblioshiny) analysis, the local and global citations of one hundred documents are provided. These (100) documents are published in 73 sources. The citation details (h and g-indexes) are provided for all sources. By Lotka’s law, we presented the frequency distribution of the productivity of authors. To describe the focus of these 100-documents, we performed the co-words analysis of titles. By biblioshiny, we presented the main focus as a thematic map and by Vosviewer, we highlighted the main co-words that appeared in the titles of the manuscripts. In this report, we bibliometrically covered 2562 publications from 2019 to May 2021.